2007
DOI: 10.1111/j.1750-3841.2007.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Varying Levels of Vegetable Juice Powder and Incubation Time on Color, Residual Nitrate and Nitrite, Pigment, pH, and Trained Sensory Attributes of Ready‐to‐Eat Uncured Ham

Abstract: Vegetable juice powder (VJP) and a starter culture containing Staphylococcus carnosus have been identified as necessary ingredients for the manufacture of uncured, no-nitrate/nitrite-added meat products with quality and sensory attributes similar to traditional cured products. The objectives of this study were to determine the effects of varying concentrations of VJP and incubation time (MIN-HOLD) on quality characteristics, including lipid oxidation, color, and cured meat pigment concentrations, of ham over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
121
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(152 citation statements)
references
References 26 publications
(28 reference statements)
23
121
2
6
Order By: Relevance
“…The results are consistent with reports of Sindelar et al (2007b), who observed constant values of NO 3 during the ripening period of cooked sausages to which only NO 2 was added. Sindelar et al (2007a) observed reduced levels of NO 3 in cooked hams that were not subjected to incubation, but not in those that were incubated.…”
Section: Physicochemical and Color Analysessupporting
confidence: 83%
“…The results are consistent with reports of Sindelar et al (2007b), who observed constant values of NO 3 during the ripening period of cooked sausages to which only NO 2 was added. Sindelar et al (2007a) observed reduced levels of NO 3 in cooked hams that were not subjected to incubation, but not in those that were incubated.…”
Section: Physicochemical and Color Analysessupporting
confidence: 83%
“…. The same author has worked with other natural or organic methods with promising results 52 . One of these methods is natural vegetable juice, which has proved quality and usefulness comparable with conventional curing methods 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Meat products with organic or natural additives without nitrites or nitrates are good alternative of consumption 54 . However several low-sodium meats obtained by physical and chemical methods have failed in sanity quality, sensory perception and consumer acceptance 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Rosemary extract has potent antioxidant activity attributed to flavonoid compounds (SEBRANEK, 2005;BOZKURT, 2006;GEORGANTELIS, 2007), while celery powder serving as a natural source of nitrite can be the primary source of natural curing ingredients (SINDELAR et al, 2007;. Given the concern about food safety by the population and the expectative of the industry for healthier alternatives, the aim of this study was to evaluate the effect of addition of rosemary extract and celery-based products in salami as substitutes of conventional curing salts on the sensory and physicochemical characteristics in different ripening times.…”
Section: Entre Os Três Tratamentos Na Matéria Seca (Ms) Proteína Brumentioning
confidence: 99%